Poems of Henry Timrod; with Memoir - Timrod, Henry, 1828-1867 (Salt Lake City, UT : Project Gutenberg, 1997)
"Poems of Henry Timrod" by Henry Timrod is a collection of lyrical poetry written in the mid-19th century that captures the essence of Southern life and sentiment during a tumultuous era in American history, particularly the Civil War. The poems reflect Timrod's deep connection to nature, love, loss, and the experiences of his people, revealing both personal and collective emotions amidst the backdrop of conflict and hope. The opening portion of the collection includes an introduction that establishes Henry Timrod as a voice of the South, emphasizing his role as a poet who articulates the spirit and struggles of his people. This section outlines his early life, influences, and the profound impact of the Civil War on his work. It suggests that his poetry is not merely artistic expression but a means of connecting with a broader historical narrative, particularly as it relates to themes of nature and human experience. Timrod's unique perspective encapsulates the beauty, challenges, and resilience of the Southern landscape and its people, setting the tone for the evocative verses that follow. (This is an automatically generated summary.)
Release date is 1997-03-01
Produced by Alan Light, and David Widger
Keywords: Timrod, Henry, 1828-1867; American poetry -- 19th century; United States -- History -- Civil War, 1861-1865 -- Poetry -- Confederate